2020
DOI: 10.1016/j.jhsg.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 30-Day Perioperative Complications for Open Operative Care of Distal Upper-Extremity Fractures Treated by Orthopedic Versus Plastic Surgeons: A Study of the National Surgical Quality Improvement (NSQIP) Database

Abstract: Purpose: To determine whether surgeon specialty affects complications after open operative care of distal upper-extremity fractures. Methods: We performed a retrospective cross-sectional study using the American College of Surgeons National Surgical Quality Improvement Database from 2005 to 2016. Patients were included if they received open operative treatment by an orthopedic or a plastic surgeon for distal radius/ulna, carpal, metacarpal, or phalangeal fracture. Univariate analysis and multivariable analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…Despite these differences in training and practice patterns, previous studies have found no difference in complication rates when comparing hand surgeons trained in orthopedic surgery or plastic surgery in the setting of upper-extremity fractures. 6 The raw complication rates calculated in this study agree with these findings. However, when taking into account the calculated morbidity and mortality rates using linear regression analysis, our study found a lower reoperation, readmission, and unplanned readmission rate in general surgery-trained hand surgeons, followed by plastics and then orthopedic surgery.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite these differences in training and practice patterns, previous studies have found no difference in complication rates when comparing hand surgeons trained in orthopedic surgery or plastic surgery in the setting of upper-extremity fractures. 6 The raw complication rates calculated in this study agree with these findings. However, when taking into account the calculated morbidity and mortality rates using linear regression analysis, our study found a lower reoperation, readmission, and unplanned readmission rate in general surgery-trained hand surgeons, followed by plastics and then orthopedic surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Data are queried through the use of Current Procedural Terminology (CPT) codes. 5,6 The NSQIP database was queried for all CPT codes related to the upper extremity distal to the elbow (24,000-26,999) between 2014 and 2018. Procedures that were not performed by a general, orthopedic, or plastic surgeon were excluded, as were polytraumas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomic locations were grouped by CPT code into procedures of the humerus (24430 and 24435), radius or ulna (25400, 25405, 25415, and 25420), and metacarpal or phalanx (26546), as is consistent with previous studies. [25][26][27]…”
Section: Inclusion Criteria Upper Extremitymentioning
confidence: 99%
“…11 Completing different residency training inevitably imparts different skill sets and can affect practice patterns after graduation from training programs. 12,13 Thus, we sought to compare operative experience of graduating chief residents in orthopedic surgery, plastic surgery, and general surgery to gain an understanding of the exposure to operative hand surgery in these fields.…”
mentioning
confidence: 99%